PENINGKATAN KETERAMPILAN MENULIS NARASI MELALUI PEMBELAJARAN KONTEKSTUAL KELAS IV SDN SUKABUMI UTARAN 04 PAGI - Fatmawati, Dede; Fatonah, Khusnul (Eduscience : Jurnal Ilmu Pendidikan, 2018)
AbstractThis study aims to improve the skills of narrative writing through contextual learning class IV SDN Sukabumi Utara 04 morning. The type of this research is Classroom Action Research (PTK). This research is conducted two cycles that each cycle consists of planning, action, observation, and reflection. The subjects of the study were the fourth grade students of SDN Sukabumi Utara 04 Pagi, which amounted to 28 students. Data collection techniques used interviews, observation, documentation, and field notes. Verify the validity of data using triangulation. Data analysis technique used is descriptive qualitative and descriptive quantitative. The results showed that the skills of students in writing narrative have increased. Percentage of students writing skill score at the end of first cycle of meeting I was 62.59% or as many as 3 students got score ≥ 75, Second Meeting was 65.71% or as many as 4 students got value ≥ 75. Percentage of student writing skill score at end of second cycle of meeting I was 73.93 % or as many as 13 students got the value ≥ 75. The second meeting was 78.84% or as many as 21 students got the value of ≥ 75. Keywords: writing skills narrative, contextual learning AbstrakPenelitian ini bertujuan untuk meningkatkan keterampilan menulis narasi melalui pembelajaran kontekstual kelas IV SDN Sukabumi Utara 04 pagi. Jenis penelitian ini adalah Penelitian Tindakan Kelas (PTK). Penelitian ini dilaksanakan dua siklus yang setiap siklusnya terdiri atas perencanaan, tindakan, observasi, danrefleksi. Subjek penelitian adalah siswa kelas IV SDN Sukabumi Utara 04 Pagi yang berjumlah 28 siswa. Teknik pengumpulan data menggunakan wawancara, observasi, dokumentasi, dan catatan lapangan. Pemeriksaan keabsahan data menggunakan triangulasi. Teknik analisis data yang digunakan adalah deskriptif kualitatif dan deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa keterampilan siswa dalam menulis narasi mengalami peningkatan. Persentase nilai keterampilan menulis siswa pada akhir siklus I pertemuan I sebesar 62.59% atau sebanyak 3 siswa mendapat nilai ≥ 75, Pertemuan II sebesar 65.71% atau sebanyak 4 siswa mendapat nilai ≥ 75. Persentase nilai keterampilan menulis siswa pada akhir siklus II pertemuan I sebesar 73.93% atau sebanyak 13 siswa mendapat nilai ≥ 75.Pertemuan II sebesar 78.84% atau sebanyak 21 siswa mendapat nilai ≥ 75. Kata kunci: keterampilan menulis narasi, pembelajaran kontekstual